Development of polyhydroxyalkanoate composites based on food industry by-products for compostable packaging - Hilliou, L. (2013)
Apresentação efetuada no "International Workshop ‘Ecosustainable Food Packaging : the Industrial Challenges’, Food and Agriculture COST Action FA0904", em Leiria, Portugal, 2013